Family Nursing Care in the Management of Ineffectiveness of Hypertension Management through Family Empowerment in the Pakusari Health Center Working Area, Jember - Aditya Kusuma Wardana Wardana; Tantut Susanto; Hanny Rasni; Achmad Ali Basri (Journal of Health Community Service, 2025)
Ineffective family health management is an unsatisfactory pattern of handling health problems in the family to restore the health conditions of family members. Family empowerment is one of the efforts that can be done to increase cognitive, affective and psychomotor through health education, physical exercise and traditional medicine. This scientific work aims to analyze nursing care with ineffective health management problems with family empowerment in handling hypertension so that families are expected to be able to provide effective family nursing care in overcoming hypertension problems with family empowerment. This study was conducted by conducting observations and demonstrations for 3 weeks with 8 meetings in three families with hypertensive family members who were given family empowerment interventions through hypertension health education, anti-hypertension exercises and cucumber juice therapy. Based on the results of research on three families, it was found that there was an increase in family cognition about hypertension and hypertension diet, there was a decrease in systole and diastole blood pressure after anti-hypertensive gymnastics and administration of cucumber juice. Family empowerment shows that there is an influence on the handling of hypertension in the family. Family empowerment is important to do because it has a positive influence on cognitive changes, changes in systole and diastole pressure of hypertensive patients. Family empowerment can be done consistently and continuously because hypertension is a chronic disease and needs family involvement.